On the static Casimir effect with parity-breaking mirrors - Fosco, Cesar Daniel (2017)
We study the Casimir interaction energy due to the vacuum fluctuations of the electromagnetic (EM) field in the presence of two mirrors, described by 2 + 1 -dimensional, generally nonlocal actions, which may contain both parity-conserving and parity-breaking terms. We compare the results with the ones corresponding to Chern–Simons boundary conditions and evaluate the interaction energy for several particular situations.